Influence of elevation and rainfall on leaf growth, bean characteristics and yield components of arabica and robusta coffee under changing climatic conditions in Karnataka state, India - Patil, Somashekhargouda; Devasia, Jeena; Daniel, George; Rao, N. Surya Prakash (Journal of Plantation Crops, 2022)
The study was undertaken to analyze the behaviour of coffee under changing climatic conditions in different coffee liaison zones of Karnataka State, India, during 2017-2020. Sample estates were identified based on elevation and rainfall patterns in different zones of the Chikkamagaluru and Hassan districts. The leaf growth parameters, bean characteristics and yield components were recorded in all the sample estates. Correlation studies indicated a significant positive relationship between the elevation, rainfall with specific leaf area (r = +0.912) and productivity (r = 0.475) during the pre-monsoon period. The monthly summer rainfall during March and April showed a significant correlation with yield in robusta (r = 0.511) and arabica (r = 0.451), indicating that blossom shower during this period significantly influenced the productivity of coffee. The studies between elevation, the quantum of rainfall and bean defect parameters indicated a significant (p<0.05) positive correlation. A positive relationship was also found between elevation and peaberry production in both robusta (r = 0.716) and arabica coffee (r= 0.456), respectively. However, there was also a significant relationship between rainfall (2020) and Jollu percentage (r = 0.386) in robusta coffee, indicating that higher elevation and rainfall-induced more peaberry content and Jollu percentage under changing climatic conditions. The overall result indicated that changes in climatic conditions such as excess rainfall and continuous soil moisture led to more vegetative growth than reproductive growth. This also produced more bean abnormalities which in turn affected the yield and quality of the coffee.